Dedikasi Ulama Hadis Abad Pertama Hijriyah: Upaya Kodifikasi dan Penyebaran oleh Sahabat dan Tabi'in - Abdurahim, Mika; Mujoko, Bejo; Azzami, Abdulloh; Kosasih, Engkos; Mighwar, Muhammad Al (Asian Journal of Islamic Studies and Da'wah, 2024)
This study seeks to explore the commitment of hadith scholars to the Companions and influential figures among the tabi'in during the first century of the Islamic calendar through the process of codifying and transmitting hadith. Hadith represents a primary source of Islamic teachings following the Quran, and its codification is crucial for preserving the integrity and authenticity of Islamic doctrines. During the early period of Islam, the Prophet's companions and the tabi'in played pivotal roles in disseminating and safeguarding hadith traditions. This study employs a qualitative approach using a descriptive-historical analysis method, drawing on primary sources such as Ashfahani's Hilyatul Auliya hadith compilation, writings of earlier scholars, and secondary sources including books, scholarly articles, and journals. The findings of the research indicate that the companions of Prophet Muhammad demonstrated significant commitment in memorizing, compiling, and transmitting hadith traditions. They employed diverse strategies to guarantee the precision and trustworthiness of the hadiths they transmitted. Similarly, the leaders among the tabi'in, as the succeeding generation, persisted in this endeavor by stressing the significance of verifying and authenticating hadiths until the compilation of collections of hadith books (tadwin/codification). They developed a more systematic methodology in the codification of hadith, which became the basis for the development of hadith science in subsequent periods. This research provides a deeper understanding of the history of hadith codification and the important role of the companions and tabi'in in this effort, as well as highlighting the importance of the methodology used to maintain the purity of hadith.